TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANTAR PRIBADI SISWA - Putra, Giri Isna; Sutarno, Sutarno; Djannah, Wardatul (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2013)
This study was a quasi-experimental design with the type of Nonequivalent Control Group Design. The sampling technique was Purposive Random Sampling Technique. Data analysis  was  using Two-Way ANOVA. Based on the testing result of hypothesis I the value of Fcount is 9,138 and Ftable was 3,92, with the significance level of 0,003<0,05. It is identified that Fcount>Ftable then Ha  was  accepted.  It  means  that  there  is  significantly  difference  in  the  ability  of interpersonal communication before being given treatment and after being given treatment. The testing result of hypothesis II the value of Fcount was 5,542  and  the  Ftable  is  3,92,  with  the significance level  of 0,020 <0,05.  It  was identified that Fcount>Ftable then Ha is accepted. It may imply that there are significantly differences in the ability of interpersonal communications in the experimental group and the control group. The testing result of sub hypothesis III the value of Fcount  is 4.850 and the Ftable  is 3.92, with the significance level of 0.034<0.05. It is identified that the Fcount > Ftable then Ha is accepted. It means that there is an interaction between groups of interpersonal communication skills on pretest and posttest with interpersonal communication skills in the experimental group and the control group.